Al-Qur’an dan Wawasan Ekologi - Ahmad, Muttaqein (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2020)
AbstractThis article examines the principles of the Qur'an related to the environment by continuing to pay attention to relationships with God and social beings, and to pay attention to the conservation of the surrounding environment. This article uses a thematic method by exploring exegetical books with various verses and interpretations of the environment. The results of this study indicate that there are six principles of the Qur'an related to the environment: 1) the principle of tauhid, the principle that nature and the environment are part of the mark of God's rudeness, 2) humans as caliph on earth, 3) the principle of trust (amanah), 4) the principle of justice , 5) the principle of harmony and 6) the principle of balance. This proves that the Qur’an teaches compatibility between spiritual and scientific paths. These six principles can also become the foundation for preventing environmental crises based on the Qur'an. AbstrakArtikel ini akan mengkaji tentang prinsip-prinsip al-Qur’an terkait lingkungan dengan terus memperhatikan relasional dengan Tuhannya dan makhluk sosial, serta mereka juga harus memperhatikan konservasi lingkungan sekitarnya. Artikel ini menggunakan metode tematik dengan menelusuri kitab-kitab tafsir dengan berbagai ayat dan penafsiran tentang lingkungan. Dari hasil penelitian, dapat ditemukan enam prinsip yang terkait lingkungan yaitu prinsip tauhid, prinsip bahwa alam dan lingkungan bagian dari tanda kebasaran Allah, manusia sebagai khalifah di bumi, prinsip amanah, keadilan dan prinsip keselarasan dan keseimbangan. Hal itu membuktikan bahwa al-Qur’an mengajarkan adanya kesesuaian antara jalan ruhani dan ilmiah. Keenam prinsip itu juga dapat menjadi pondasi dalam mencegah krisis lingkungan yang berlandaskan al-Qur’an.Kata Kunci: Konservasi Lingkungan, Wawasan dan Ayat Ekologi.